Analysis of the S2 ← S0 vibronic spectrum of the ortho-cyanophenol dimer using a multimode vibronic coupling approach - Kopec, Sabine; Ottiger, Philipp; Leutwyler, Samuel; Köppel, Horst (The journal of chemical physics, 2015)
The S2←S0 vibronic spectrum of the ortho-cyanophenol dimer (oCP)2 is analyzed in a joint experimental and theoretical investigation. Vibronic excitation energies up to 750 cm−1 are covered, which extends our previous analysis of the quenching of the excitonic splitting in this and related species [Kopec et al., J. Chem. Phys. 137, 184312 (2012)]. As we demonstrate, this necessitates an extension of the coupling model. Accordingly, we compute the potential energy surfaces of the ortho-cyanophenol dimer (oCP)2 along all relevant normal modes using the approximate second-order coupled cluster method RI-CC2 and extract the corresponding coupling constants using the linear and quadratic vibronic coupling scheme. These serve as the basis to calculate the vibronic spectrum. The theoretical results are found to be in good agreement with the experimental highly resolved resonant two-photon ionization spectrum. This allows to interpret key features of the excitonic and vibronic interactions in terms of nodal patterns of the underlying vibronic wave functions.